Efficient Pd-Catalyzed Hydrodehalogenation of o-Haloanilides in Water - Tang, Yanling; Li, Minxin; Gao, Hui; Rao, Gaoxiong; Mao, Zewei (Synlett, 2020)
In the present work, we have developed a practical methodology for the hydrodehalogenation of o-haloanilides using PdCl2 at 100 °C under mild conditions in water. The catalytic system could selectively dehalogenate both aryl chloride and aryl bromide and exhibit a broad functional group tolerance.
Keywords: Pd-catalyzed; dppap; hydrodehalogenation; o-haloanilides; water